New Mexico Poetry Anthology 2023 - Romero, Levi; Otero, Michelle; New Mexico State Library Poetry Center (Santa Fe, New Mexico Museum of New Mexico Press, Santa Fe, 2023)
"New Mexico Poetry Anthology 2023 is an "ode and homage to nuestra querencia, our beloved homeland." More than two hundred poems explore themes such as community, culture, history, identity, landscape, and water. From a diverse group of poets, the poems are introspective and personal; reflective and astute; steady and celebratory. Including poignant, unique, even humorous perspectives on life in New Mexico influenced by the COVID-19 pandemic, this collective of voices serves as a welcome remedio to all aspects of post-pandemic life, for ears aching for words of beauty, strength, and solace as we emerge from the cocoon of survivability."
113484
Keywords: Poetry -- Anthologies (multiple authors); Poetry -- Subjects & Themes -- Places; Literary Collections; New Mexico -- Poetry; New Mexico; Poetry